2015
DOI: 10.1517/14728222.2015.1053208
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of phosphorylated proto-oncogeneCREBat Ser 133 site inhibits growth and metastatic activity of renal cell cancer

Abstract: These data suggest that decreasing the level of pCREB inhibits the growth and metastasis of RCC by targeting the Ser 133 site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 52 publications
4
23
0
Order By: Relevance
“…Previous reports showed that CREB promoted cancer metastasis (12,14,43,44). CREB regulated vascular endothelial growth factor expression and was involved in human prostate cancer bone metastasis (45).…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports showed that CREB promoted cancer metastasis (12,14,43,44). CREB regulated vascular endothelial growth factor expression and was involved in human prostate cancer bone metastasis (45).…”
Section: Discussionmentioning
confidence: 95%
“…CREB, a common downstream target of AKT, is a proto-oncogenic transcription factor, which generally regulates various cell functions by enhancing the expression of target genes [32,33]. Our previous studies indicated that the over-expression and abnormal activation of CREB celebrate tumorigenesis and tumor migration [34,35]. Therefore, we postulated that overexpression of PNN promotes prostate cancer progression through activating PI3K/AKT/CREB signaling axis.…”
Section: Pnn Regulates Prostate Cancer Cell Proliferation and Migratimentioning
confidence: 96%
“…Our previous study demonstrated that pCREB was upregulated in human renal cancer cell lines and tissues. Lentiviral vector production was used to knockdown the expression of pCREB in OS-RC-2 cells and the results demonstrated that decreasing the level of pCREB inhibited the growth and metastasis of OS-RC-2 cells (21). However, although the results are promising, further studies are needed to confirm this.…”
Section: Cyclic Amp Responsive Element-binding Protein Induces Metastmentioning
confidence: 99%